Cloning and expression in Escherichia coli of pectinase genes of Erwinia carotovora subsp. carotovora. - Zink, R T (1985)
Genes coding for an endo-pectate lyase, an exo-pectate lyase, and an endopolygalacturonase of Erwinia carotovora subsp. carotovora Ecc71 were cloned in Escherichia coli HB101, using the cosmid pHC79. The products of the cloned pectinase genes paralleled their counterparts in strain Ecc71 in isoelectric mobility, mode of substrate degradation, and ability to macerate potato tuber tissue.